Diagnostic Model of Superficial Lymph Nodes Based on Clinical History and Ultrasound Findings: A Prospective Cohort Study - Tan, Xiao-Qu; Qian, Lin-Xue; Zhao, Jun-Feng; Sun, Peng-Fei; Li, Qing-Qing; Feng, Ruo-Xuan (Frontiers in Oncology, 2022)
Objectives: Differentiation of benign and malignant changes in lymph nodes is extremely important. We aimed to identify the ultrasound and clinical diagnostic criteria permitting this differentiation. Methods: Clinical and ultrasound data were collected at Beijing Friendship our hospital Hospital from May 2019 to November 2020. Univariate and multivariate analysis were performed using statistical methods, and a mathematical model was established to evaluate benign and malignant lymph nodes. Results: A total of 1343 LNs (person) with US‐guided core needle or fine needle biopsy (CNB or FNB) were evaluated in the analysis. Variables with a high predictive power were sex (odds ratio, OR: 3.360, p<0.001), short diameter (OR: 4.660, p<0.001), short/long diameter (S/L) ratio (OR: 1.515, P=0.007), border (OR: 1.626, p=0.002), cortex echogenicity (OR: 2.089, P<0.001), fusion (OR: 2.313, p=0.002), vascularity (peripheral vascularity, OR: 3.424, p<0.001; mixed vascularity, OR: 4.127, p<0.001), and medical history (fever/local pain, OR: 0.316, p<0.001; tumor history in the drainage area, OR: 4.595, p<0.001; both, OR: 5.554, p<0.001). The cut-off score on receiver operating characteristic (ROC) curve analysis using these eight variables was 2.5. The largest area under the ROC curve (Az) value was 82.3% (95% confidence interval (CI), 0.805–0.851), and the sensitivity (79.4%), specificity (72.3%), and accuracy (74.8%) were higher than those for nearly all the single indices. Conclusion: The model of combination of ultrasound and clinical symptoms can preliminarily evaluate the benign and malignant of lymph nodes.Malignant tumors can be diagnosed in patients meeting ≥3 of the following criteria (≥4 criteria for patients with only fever or local pain): (1) male sex, (2) history of tumor in the drainage area, (3) short diameter ≥ 0.8 cm, (4) S/L ratio ≥ 0.5, (5) blurred border, (6) inhomogeneous cortical echo, (7) peripheral or mixed vascularity, and (8) lymph node fusion.